Challenges in Sr2FeMoO6−δ Thin Film Deposition. Issue 3 (8th October 2019) - Suchaneck, Gunnar; Kalanda, Nikolay; Artsiukh, Evgenij; Gerlach, Gerald
Abstract : This work reviews some fundamental issues that are relevant for the fabrication of stable‐phase strontium ferromolybdate thin films. The main challenges for strontium ferromolybdate thin film deposition arise from the sensitivity of the material's magnetic properties to point defect formation: i) Antisite defect formation and oxygen nonstoichiometry should be avoided by precise composition control during film manufacturing; ii) a highly ordered state of the correct phase and B‐site cation valence will be obtained only in a very narrow window of growth conditions; iii) to avoid additional antisite disorder with decreasing synthesis temperature, the effective temperature at the film surface should be increased by an energy flux to the growing film surface. Since thin film deposition is nonequilibrium in nature, the review starts with the consideration of equilibrium phase stability. Cation and oxygen stoichiometries are analyzed with regard to their effect on key magnetic properties. Film strain formed due to thermal and lattice mismatch is of great concern since it influences the choice of the substrate. Finally, thin film deposition techniques are valued for their benefits in strontium ferromolybdate thin film technology. Abstract : This work reviews some fundamental issues that are relevant for the fabrication of stable‐phase strontium ferromolybdate thin films. The review starts with the consideration of equilibrium phase stability. Cation and oxygen stoichiometries are analyzed with regard to their effect on key magnetic properties. Finally, thin film deposition techniques are valued for their benefits in strontium ferromolybdate thin film technology.